Microbiological profile of causes of corneal ulcers at sultan agung islamic teaching hospital semarang (Bangladesh Journal of Medical Science, 2024)
Background: Corneal ulcer is a medical condition that is the most significant cause of morbidity and blindness worldwide, caused most often by bacteria and fungi. This study aimed to determine the microbiological profile of the causes of corneal ulcers at Sultan Agung Islamic Teaching Hospital, Semarang.Methods: This research is a descriptive study with a cross-sectional design. Samples were all patients with corneal ulcers at Sultan Agung Islamic Teaching Hospital Semarang from July 1, 2018 – July 31, 2023; the sampling method used consecutive sampling, and the  sample  size  was  the  total  population.  Samples  were  taken using a scraping on the cornea, then implanted directly in Blood Agar Plate and Saboroud Dextrose Agar. Bacterial colonies are identified using API®, and a susceptibility test was performed on Muller Hinton Agar using the Kirby Bauer method. Fungal colonies are identified using Lacto Phenol Cotton Blue, Gram, and Germ Tube.Results: There were 85 samples, with no growth as many as 41 samples (48%).  Fungi  cause more infections than bacteria. The fungus that causes the most extensive corneal ulcers is Aspergillus sp as  much  as  13,  while  the  group  of  bacteria  is  Staphylococcus coagulase negative as much as 4 (50%)Conclusion: Most of the microorganisms that cause corneal ulcers are fungi compared  to  bacteria.  No  Multi-Drug  Resistant  Organisms were found in the causative bacteria, and no azole resistance was found in fungi.  Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 676-681